Hematological profile of East African short-horn zebu calves from birth to 51 weeks of age - Wyk, Ilana Conradie van; Goddard, A.; Bronsvoort, B.M. de C.; Coetzer, Jacobus A.W.; Booth, C.; Hanotte, Olivier H.; Jennings, A.; Kiara, Henry K.; Mashego, P.; Muller, C.; Pretorius, G.; Poole, Elizabeth J.; et al. (Springer, 2013)
This paper is the first attempt to accurately describe the hematological parameters for any African breed of cattle, by capturing the changes in these parameters over the first 12 months of an animal’s life using a population based sample of calves reared under field conditions and natural disease challenge. Using a longitudinal study design, a stratified clustered random sample of newborn calves was recruited into the Infectious Diseases of East African Livestock (IDEAL) study and monitored at 5-weekly intervals until 51 weeks of age. The blood cell analysis performed at each visit included: packed cell volume; red cell count; red cell distribution width; mean corpuscular volume; mean corpuscular hemoglobin concentration; hemoglobin concentration; white cell count; absolute lymphocyte, eosinophil, monocyte, and neutrophil counts; platelet count; mean platelet volume; and total serum protein. The most significant age-related change in the red cell parameters was a rise in red cell count and hemoglobin concentration during the neonatal period. This is in contrast to what is reported for other ruminants, including European cattle breeds where the neonatal period is marked by a fall in the red cell parameters. There is a need to establish breed specific reference ranges for blood parameters for indigenous cattle breeds. The possible role of the postnatal rise in the red cell parameters in the adaptability to environmental constraints and innate disease resistance warrants further research into the dynamics of blood cell parameters of these breeds